2021
DOI: 10.1039/d1ra06002c
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Brønsted and Lewis acidity on phosphated titanium dioxides for efficient conversion of glucose to 5-hydroxymethylfurfural

Abstract: Tunable Lewis and Brønsted acid sites on P–TiO2 tandem catalysts for glucose-to-HMF conversion providing high HMF yield (72%) and selectivity (83%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 72 publications
1
3
0
Order By: Relevance
“…[20] The glucose conversion (43 %) and 5-HMF yield (18 %) were improved in the biphasic system because the side reactions are suppressed by in situ extraction of 5-HMF product to an organic layer. [12,21,36] The results confirmed that the biphasic NaCl-H 2 O/n-butanol system was suitable for further study. Moreover, the blank test provided glucose conversion with a low 5-HMF yield.…”
Section: Catalytic Performance Of Mpo/al-sba-15supporting
confidence: 56%
See 1 more Smart Citation
“…[20] The glucose conversion (43 %) and 5-HMF yield (18 %) were improved in the biphasic system because the side reactions are suppressed by in situ extraction of 5-HMF product to an organic layer. [12,21,36] The results confirmed that the biphasic NaCl-H 2 O/n-butanol system was suitable for further study. Moreover, the blank test provided glucose conversion with a low 5-HMF yield.…”
Section: Catalytic Performance Of Mpo/al-sba-15supporting
confidence: 56%
“…The 5‐HMF yield from the monophasic system was low (approximately 8 %) due to undesired rehydration of 5‐HMF to by‐products [20] . The glucose conversion (43 %) and 5‐HMF yield (18 %) were improved in the biphasic system because the side reactions are suppressed by in situ extraction of 5‐HMF product to an organic layer [12,21,36] . The results confirmed that the biphasic NaCl‐H 2 O/ n ‐butanol system was suitable for further study.…”
Section: Resultsmentioning
confidence: 66%
“…For example, doping TiO 2 with metal oxides, such as SiO 2 , ZrO 2 , WO 3 , Al 2 O 3 , and V 2 O 5 , has been reported to increase the acidity of the surface and catalytic activity [18][19][20][21][22]. In addition, studies have reported the modification of the surface of TiO 2 by introducing functional groups via chemical treatment such as PO 4 3and SO 4 2- [23][24][25]. In addition, the surface properties of the support affect its interaction with the supported metal.…”
Section: Introductionmentioning
confidence: 99%
“…Homogeneous Lewis acids such as AlCl 3 , CrCl 3 , and rare earth triflates also catalyze the reaction, but difficulties in their separation and recovery remain a major drawback as well as homogeneous Brønsted acids. [9,10] Water-tolerant Lewis acid sites on Nb 2 O 5 •nH 2 O [11][12][13][14] and TiO 2 [15][16][17][18][19][20] were found to be effective for glucose dehydration in water and HMF yields were significantly improved after the introduction of phosphate groups on their surfaces. Water is DOI: 10.1002/sstr.202200224 Acid-base properties of amphoteric crystalline YNbO 4 , which is synthesized by co-precipitation method using a water-soluble Nb peroxo complex, are adjusted by the impregnation of phosphate groups.…”
Section: Introductionmentioning
confidence: 99%
“…Water‐tolerant Lewis acid sites on Nb 2 O 5 · n H 2 O [ 11–14 ] and TiO 2 [ 15–20 ] were found to be effective for glucose dehydration in water and HMF yields were significantly improved after the introduction of phosphate groups on their surfaces. Water is supposed to deactivate or decompose Lewis acid sites on metal oxides by the formation of very stable Lewis acid‐water adducts or metal hydroxide species, respectively.…”
Section: Introductionmentioning
confidence: 99%